Non-coding parts of genomes as the basis of epigenetic heredity - R. N. Mustaﬁn; E. K. Khusnutdinova (Вавиловский журнал генетики и селекции, 2017)
We hypothesized that the basis of epigenetic regulation of genomes in ontogenesis is the speciﬁcity of the distribution, number and composition of transposons. Transposons constitute the major part of the genomes of multicellular eukaryotes. The evolutionary preservation of transposons is associated with universal mechanisms for controlling cell diﬀerentiation: processing of non-coding RNAs and splicing regulation. These universal mechanisms were originally aimed at protecting against viruses and transposons. The cooperation of these protective systems with mechanisms for controlling the interrelation of cells and their diﬀerentiation became the basis for the emergence and evolution of multicellular eukaryotes. The evolutionary conservation of a complex enzymes Drosha, Dicer, Argonaut, RdRP and their homologues in all multicellular eukaryotes, and their absence in unicellular organisms supports this assumption. Introns originated from mobile genetic elements. Transposons played an important role in the propagation of introns in evolution and their regulation in ontogenesis. Transposons regulate the expression of genes in cis and in trans, and also indirectly by the production of small RNAs that aﬀect their own activity, both by altering the DNA methylation and modifying histones, and at the posttranscriptional level. Tissue-speciﬁc and stage-speciﬁc changes in the activity of transposons in ontogenesis are associated with the expression of transposon-derived noncoding RNAs and altering the activity of genes, which leads to cell diﬀerentiation. We proposed that the species-speciﬁc features of activation of transposons for each subsequent cell division undergo evolutionary selection and are key regulators of the growth and development of the organism. We proposed that transposons in the genome aﬀect their inherited activation in each subsequent cell division, which causes a change in cell diﬀerentiation.